2020
DOI: 10.1177/0253717620930315
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Mind Deficits and Their Influence on Functional Impairment in Remitted Phase of Bipolar Disorder

Abstract: Background: Functional impairment has been convincingly established in the euthymic/ remitted phase of bipolar disorder (BD). Though deficits in social cognition, especially theory of mind (ToM), predict functional impairment, the association has not been consistently proven. Methods: Thirty remitted subjects with BD (as per DSM 5) and 30 age- and gender-matched healthy controls were screened for eligibility and the sociodemographic details and ToM scores, that is, first-order ToM, second-order ToM, and Faux p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(107 reference statements)
1
0
0
Order By: Relevance
“…Another study by Palaniappan et al . [ 92 ] also found similar results in their investigation of 30 patients of bipolar disorder compared with age- and gender-matched controls on domains of theory if mind. The study reported deficits in all domains in patients with bipolar disorder.…”
Section: Resultssupporting
confidence: 56%
“…Another study by Palaniappan et al . [ 92 ] also found similar results in their investigation of 30 patients of bipolar disorder compared with age- and gender-matched controls on domains of theory if mind. The study reported deficits in all domains in patients with bipolar disorder.…”
Section: Resultssupporting
confidence: 56%